2005
DOI: 10.1088/0957-4484/16/4/012
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic effect of single-wall carbon nanotubes on the hydrogen sorption properties of sodium alanates

Abstract: Single-wall carbon nanotubes (SWNTs) were examined as catalysts for improving the hydrogen absorption and desorption properties of Ti/Zr-doped NaAlH4 hydride, proposed as a reversible hydrogen storage material. We studied the hydrogen charge and discharge characteristics and stability of sodium aluminium composites ball milled with carbon additives such as SWNTs, graphite or activated carbon (AX-21). The SWNT–NaAlH4 system was tested at 160 °C for up to 200 cycles, and the sorption kinetics were enhanced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 19 publications
2
46
0
Order By: Relevance
“…It was believed that carbon would favour a more efficient catalyst particle distribution. Moreover, recent studies have demonstrated that co-milling metal hydrides with carbon improves hydrogen sorption kinetics [10][11][12][13][14][15][16], suggesting that carbon plays a catalytic role. Zr 7 Ni 10 was chosen for the experiment, among the Zr x Ni y catalysts investigated in this work, because this particular composition is easier to activate, thus easier to turn into a fine powdery form.…”
Section: Samplementioning
confidence: 99%
“…It was believed that carbon would favour a more efficient catalyst particle distribution. Moreover, recent studies have demonstrated that co-milling metal hydrides with carbon improves hydrogen sorption kinetics [10][11][12][13][14][15][16], suggesting that carbon plays a catalytic role. Zr 7 Ni 10 was chosen for the experiment, among the Zr x Ni y catalysts investigated in this work, because this particular composition is easier to activate, thus easier to turn into a fine powdery form.…”
Section: Samplementioning
confidence: 99%
“…As for a supporting material for the deposition of metal nanocatalysts, SWNTs was used because it was reported that SWNTs can act as catalysts to improve the hydrogen absorption and desorption properties of metallic catalyst-doped hydrides [14,15].I tw a s also reported that the nanotube length decreases with increasing ball milling time [16]. In order to prevent the thorough destruction of SWNTs during the high energy milling, a short milling time of 20 min was applied for mixing the milled MgH 2 -BCN composite and the SWNTs-supported Ni/Pd catalysts in this study.…”
Section: Structural Characterization Of Mechanically Milled Mgh 2 Andmentioning
confidence: 99%
“…Several groups have investigated the use of carbon materials as possible catalysts for NaAlH 4 , and samples were almost exclusively ball milled (10)(11)(12)(13)(14). Four of these groups report that carbon materials are catalysts for the dehydrogenation and rehydrogenation of NaAlH 4 (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Four of these groups report that carbon materials are catalysts for the dehydrogenation and rehydrogenation of NaAlH 4 (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%